Evaluation of patient specific care needs during treatment for head and neck cancer. (November 2020) - Schorn, Lara; Lommen, Julian; Sproll, Christoph; Krüskemper, Gertrud; Handschel, Jörg; Nitschke, Julia; Prokein, Benjamin; Gellrich, Nils-Claudius; Holtmann, Henrik
Highlights: There is an alarming lack of rehabilitative therapies during acute HNC treatment. Strong social bonds have a positive effect on coping with HNC. Financial losses are already present during hospitalization for acute treatment. Awareness towards patients' care needs has to be improved. Abstract: Background: Tumorous diseases of the head and neck region annually occur in more than 550.000 cases worldwide. Little is known about patient specific care needs and potential relationships between non-fulfillment of those following therapeutic and especially surgical treatment of head and neck cancer (HNC). Objectives: This study aimed to evaluate potential correlations between patient specific care needs, regarding physiological rehabilitation, family/social support, economic needs, and their impact on health-related quality of life (HRQoL). Methods: A total of 1359 patients were included in this retrospective analysis. Data derived from the exploratory international multicenter rehabilitation study of the German-Austrian-Swiss Cooperative Group on Tumors of the Maxillofacial Region (DÖSAK), including 43 oral and maxillofacial departments in Germany, Austria, and Switzerland using the Bochum patient questionnaire on rehabilitation and a questionnaire on tumor and treatment related data. Results: Results showed a significant correlation of a patient's social bonds and depression, coping with depression, and anxiety. Patients' needs for speech therapy, physiotherapy or respiratory training were hardly ever met and patients had to compensate for financial losses during hospitalization for acute treatment. Conclusion: In conclusion, this study describes social, physical, and socio-economic care needs. A multidisciplinary approach managing cancer and treatment related side effects is necessary, as well as enhanced awareness of care needs of practitioners during early recovery after surgery.